Machine learning model to predict slump, VEBE and compaction factor of M-Sand and shredded PET bottles concrete - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Ali, Maisarah (IOP Publising Ltd, 2021)
This paper aims to develop the machine learning model with the help of experimental data such as slump, VEBE and compaction factor of concrete incorporated with shredded Polyethylene Terephthalate (PET) bottles, Manufactured Sand (M-sand) and River sand as find aggregates replacement in concrete mixtures. The machine learning model is developed by using different machine learning techniques such as multiple regression and decision tree.